Resilience and Psychomotricity: inclusion strategies in Preschool Education - Lourdes Cró, Maria de; Mafalda Castro Pinho, Ana (Arena-Journal of Physical Activities, 2017)
With this article we would like to deepen the resilience and psychomotricity as inclusion strategies in preschool education. We analyse too the importance of resilience and psychomotricity and their impact in the learning of disad- vantaged children at a preschool age that are exposed to adverse social and personal factors and to assess the efficiency of an intervention program based in psychomotricity and resilience together. We developed a project in a region of Brazil (Botucatu), where a Psychologi- cal Development Activation Model was used with psychomotricity exercises and also the Programme Strong Start Pre K, in the area of resilience. The assessment instruments used were the WeBeST test for resilience and the Operational Portage Inventory test for Psychomotricity. The study is longitudinal, quasi-experimental, with an experimental group (subject to Strong Start Pre K Programme for assessing resilience) and a con- trol group (not subject to the Programme), with pre and post tests given to both groups. These groups were assessed before (pre-test) and after (post- test) the manipulation of the independent variable. The results indicate that there was an evolution in resilience among children in the group that participate in this program. They improved the resilience capacity, dealing with problems and controlling the emotions. To finalise, we recommend that the training of professionals who work in education and health should include the promotion of resilience in their cur- riculum, as well as the implementation of psychomotricity and the study of emotions and feelings in order to better deal with the adversities in life.